Prooxidative and fluorescence properties of paracetamol during interactions with mitochondria. Issue 1 (2011) - Tomečková, Vladimíra; Gajová, Alena; Veliká, Beáta; Saxunová, Lýdia; Hertelyová, Zdenka
Abstract : This study was carried out to investigate isolated liver mitochondrial functions after paracetamol administration by monitoring of liver mitochondrial fluorescence properties as well as prooxidative properties of paracetamol. Paracetamol was administered to rat (in subtoxic 500 mg·kg −1 dose) in vivo . The effect of this dose was compared with the subtoxic and toxic dose of paracetamol added to mitochondria in vitro (1 and 1.5) mg paracetamol/mg mitochondrial protein. Subtoxic dose of paracetamol in vitro did not change mitochondrial fluorescence, but it significantly decreased mitochondrial fluorescence in vivo in comparison with control mitochondrial group. Toxic dose of paracetamol in vitro significantly decreased mitochondrial fluorescence. The enzymatic activity of superoxide dismutase (SOD) significantly decreased after paracetamol administration in vitro and in vivo . While both activities of glutathione peroxidase (GPx) and glutathione reductase (GR) significantly increased in dependence upon paracetamol doses. Our experiment showed, that paracetamol participates in formation of free radicals and confirms previous studies, in which paracetamol administration caused elevation of antioxidative enzymes activities in dependence on dose, which is considered therapeutically as subtoxic and toxic.